Seni Ala Sufu dalam Pendekatan Diri Kepada Tuhan dan Implikasinya dalam Psikioterapi Islam - Nuraini A. Manan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Art is a medium for the achievement of spiritual truth, its position can be  compared with philosophy. Religion, art and philosophy are among the world  which allows people who regarded as the material can enter into spiritual nature or  spiritual nurture. The totality of one’s self and consolidation to achieve the  essence of the spiritual nature can be realized with the arts as a tool. Sufi worlds  have proven how the servants of Allah SWT reach the creator through language  and art activities. Al-Hallaj band al-Rabiah Adawiyah relied their live to God and  explained the beautiful of ma’rifah through poetic. Likewise with Jalaludin Rumi,  who enjoyed the existence of God through religious dances. Not all of us can  understand the nuances of pleasure and mortality experienced by the Sufi’s, but to explore the beauty of language and meaningful religious dance, will make our  souls fly to the spiritual sense. Sufi’s life was identical with the value of beauty in  the art in the form full of philosophical meaning. The expressions of beauty and  love are manifested in the form of Sufi poetry and dance, its aim to show how  much love of Sufi to Allah SWT. In remembrance of a long and deep con- templation of the nature of the creator, the Sufis came to the place which enable  them to open the veil between himself and their great creator, so that they reached  the climax of human self-awareness; there was only themselves in the mortality  together with their loved one.